Using the transformation Hough detection of illicit traffic facilities - Вовк, В. Ю.; Коляденко, О. А.; Гончарук, О. М.; Семенов, О. О. (Problems of Informatization and Control, 2010)
The classical and generalized transformation Hough algorithms and their possible use in problems of detection of illicit transportation of items are considered here. Also, we can talk about the parameters that affect the quality of the algorithm and possible improvement of qualitative parameters of the al-gorithm